2008
DOI: 10.1097/mlr.0b013e3181653d6b
|View full text |Cite
|
Sign up to set email alerts
|

Hospital Volume, Surgeon Volume, and Patient Costs for Cancer Surgery

Abstract: High surgeon volume, rather than high hospital volume is associated with lower inpatient cancer surgery costs, and the relationship has become significant in recent years for each cancer procedures examined. These data suggest that cost savings are best achieved through a surgeon-specific referral program.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
65
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(68 citation statements)
references
References 31 publications
2
65
1
Order By: Relevance
“…A more recent study found a statistically significant cost reduction of $5,935 for a PD performed by a HV surgeon (>5 PDs/ year) compared to a LV surgeon (1 PD/year), but found no significant cost difference by hospital volume. 11 This cost difference between HV and LV surgeons was close to the cost difference of $5,820 found in our study, although our study did not reach statistical significance likely due to a smaller number of patients.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…A more recent study found a statistically significant cost reduction of $5,935 for a PD performed by a HV surgeon (>5 PDs/ year) compared to a LV surgeon (1 PD/year), but found no significant cost difference by hospital volume. 11 This cost difference between HV and LV surgeons was close to the cost difference of $5,820 found in our study, although our study did not reach statistical significance likely due to a smaller number of patients.…”
Section: Discussionsupporting
confidence: 78%
“…The impact of surgeon volume, independent of institutional experience, has been more difficult to establish, but several studies have indicated that surgeon volume can be an independent predictor of improved outcome after PD. [8][9][10][11][12] Despite this abundant literature and the demonstration of some trends toward regionalization of care, the majority of PDs are still performed in community hospitals by surgeons with varying degrees of experience. [12][13][14] The number of PDs that categorizes an institution as high volume varies within the literature.…”
Section: Introductionmentioning
confidence: 98%
“…There is little evidence in the literature of an association between hospital volume and lower average patient costs (Posnett 1999). However, Ho and Aloia (2008) examined the relationship between patient costs and both hospital volume and surgeon volume for six cancer surgery resections. They found that patient costs were lower at high-volume hospitals compared with low-volume hospitals for only one of the six procedures; conversely, high surgeon volume was associated with lower patient costs for all six procedures.…”
Section: Discussionmentioning
confidence: 99%
“…A high hospital volume and use of clinical pathways were predictors for riskadjusted length of stay for total knee arthroplasties in Japan [31]. High surgeon volume, rather than hospital volumes, was associated with lower in-patient costs in cancer surgery [32]. In oral cancer reconstruction operations, a low surgeon volume was associated with higher costs per patient [33].…”
Section: Provider Volume As a Determinant Of Resource Use And Outcomementioning
confidence: 97%